2015
DOI: 10.1371/journal.pone.0139206
|View full text |Cite
|
Sign up to set email alerts
|

Substance P and Chronic Pain in Patients with Chronic Inflammation of Connective Tissue

Abstract: ObjectiveEvidence suggests that substance P (SP) is involved in chronic joint inflammation, such as the pathogenesis of rheumatoid arthritis and osteoarthritis. The goal of the research was to evaluate the correlation between chronic pain and changes in the SP level in patients with chronic inflammation of the connective tissue.MethodsPatients with osteoarthritis and rheumatoid arthritis were enrolled in this study. The relationship between chronic pain intensity and the serum SP concentration was evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 28 publications
5
23
0
1
Order By: Relevance
“…Thus, the conclusion that SP levels are not associated with pain history should be interpreted with caution. Chronic elevation of SP may be a better marker of chronic pain (Lisowska et al , 2015) that is often managed at home and this was not assessed in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the conclusion that SP levels are not associated with pain history should be interpreted with caution. Chronic elevation of SP may be a better marker of chronic pain (Lisowska et al , 2015) that is often managed at home and this was not assessed in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Chronic inflammation is a common symptom in OA (osteoarthritis) and RA. A study by Barbara et al (61) found that serum SP concentration in patients with OA and RA was positively correlated with the intensity of chronic pain.…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…SP is a crucial mediator of inflammation, and plays a key role in the generation and maintenance of inflammation. It is involved in the pathophysiology of various inflamatory diseases such as rheumatoid arthritis and joint inflammation (11,12). SP participates in the inflammatory processes by inducing the release of proinflammatory cytokines such as IL-1, IL-2 and TNF-α from various cells (13).…”
Section: The Comparison Of Effects Of Applications Of Compound 48/80 mentioning
confidence: 99%